Ageing Labour Forces: Promises and Prospects - Shalla, Vivian (Labour / Le Travail, 2010)
The article reviews the book, "Ageing Labour Forces: Promises and Prospects," edited by Philip Taylor.
Keywords: AGE & employment; AGEING Labour Forces: Promises & Prospects (Book); BOOKS – Reviews; Nonfiction; TAYLOR; Philip